Effekter av "Billigaste väg" för Stora Enso Skogs transportverksamhet - Bäck, Martin (SLU/Dept. of Forest Resource Management, 2008)
Transportation constitutes a large part of the forest industry's raw material costs. Transport also contributes a significant proportion of the carbon dioxide emissions. In order to reduce both the cost and environmental impact different types of decision support are required. These, in turn, require extensive information about the road network and correct information on road path selection and transport distances. In the development of national road data base for forestry (SNVDB) a road selection application has been included. The road selection application states chosen roads and distances between two points.